Anticancer Effect of Spices Used in Mediterranean Diet: Preventive and Therapeutic Potentials - Talib, Wamidh H.; AlHur, Mallak J.; Al.Naimat, Sumaiah; Ahmad, Rawand E.; Al-Yasari, Arkan Hadi; Al-Dalaeen, Anfal; Thiab, Samar; Mahmod, Asma Ismail (Frontiers in Nutrition, 2022)
Cancer is one of the leading causes of death worldwide, with almost 10 million cancer-related deaths worldwide in 2020, so any investigation to prevent or cure this disease is very important. Spices have been studied widely in several countries due to their therapeutic uses. This review highlighted chemo-therapeutic and chemo-preventive effect of ginger, pepper, rosemary, turmeric, black cumin and clove. Moreover, the mechanisms of action for each one of them were figured out such as anti-angiogenesis, antioxidant, altering signaling pathways, induction of cell apoptosis, and cell cycle arrest, for several type of cancer.